Soft X-ray and Low Energy Electron Induced Damage to DNA under N(2) and O(2) Atmospheres - Alizadeh, Elahe (2011)
DNA damage induced by low energy electrons (LEEs) and soft X-rays is measured under dry nitrogen and oxygen at atmospheric pressure and temperature. Five-monolayer plasmid DNA films deposited on tantalum and glass substrates are exposed to Al K(α) X-rays of 1.5 keV in the two different environments. From the damage yields for DNA, G-values are extracted for X-rays and LEEs. The G values for LEEs are 3.5 and 3.4 higher than those for X-ray photons under N(2) and O(2) atmospheres, respectively. Since most of the measured damage is in the form of single strand breaks (SSB), this result indicates a much higher effectiveness for LEEs relative to X-rays in causing SSB in both environments. The results indicate that the oxygen fixation mechanism, which is highly effective in increasing radiobiological effectiveness, under aerobic conditions, is operative on the type of damage created at the early stage of DNA radiolysis by LEEs.